Poza marginesem. Pamięć i reprezentacje przeszłości w materiałach źródłowych Polskiego atlasu etnograficznego - Drożdż, Anna (Studia Etnologiczne i Antropologiczne, 2016)
In this paper I discuss the possibilities of interpreting the archival materials of the Polski atlas etnograficzny by means of modern theories of memory. Referring to the theory of representation, memory locations or microhistory, new contexts of the functioning of phenomena or behaviours that are studied may be found in the records that were collected. The value of the source materials is not only in their substantive content but also in the scale of research with which they were collected. The atlas data, despite all their limitations, provide ample opportunities for the interpretation of such representations of the past, being a true reservoir of them. In many cases they require an individual approach, the knowledge of the specific context and a presentation of the interpretations in the form of a specific microhistory. Some, however, are experienced by a larger group of people, thus legitimizinginferences of a more general nature.